2000
DOI: 10.1016/s0378-1097(00)00473-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid-adaptation on Listeria monocytogenes survival and translocation in a murine intragastric infection model

Abstract: Acid tolerance response mechanisms can greatly influence Listeria monocytogenes survival in low pH foods. In the present paper, the effect of acid-adaptation together with control of gastric pH level on L. monocytogenes survival and translocation was analyzed after intragastric inoculation in the BALB/c mouse model. Our results showed that acid-adaptation led to an increase in resistance to the first barrier constituted by the low gastric pH and that inoculation at alkaline pH had a synergistic effect. It resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 10 publications
(14 reference statements)
2
20
0
Order By: Relevance
“…We previously demonstrated that the expression of virulence determinants of L. monocytogenes can be influenced by low temperature and iron deficiency (10,11,12). Sensing an acidic environment, as that encountered by the bacterium during passage through the gastrointestinal tract, can be considered an additional stimulus triggering expression of the virulent phenotype, and this is consistent with the evidence that induction of the ATR enhances the survival of L. monocytogenes both in vitro and in vivo (9,16,39,43,49). Acid-tolerant variants have increased lethality for mice when inoculated by the intraperitoneal route (43).…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We previously demonstrated that the expression of virulence determinants of L. monocytogenes can be influenced by low temperature and iron deficiency (10,11,12). Sensing an acidic environment, as that encountered by the bacterium during passage through the gastrointestinal tract, can be considered an additional stimulus triggering expression of the virulent phenotype, and this is consistent with the evidence that induction of the ATR enhances the survival of L. monocytogenes both in vitro and in vivo (9,16,39,43,49). Acid-tolerant variants have increased lethality for mice when inoculated by the intraperitoneal route (43).…”
Section: Discussionsupporting
confidence: 64%
“…As in other bacteria, the ATR in L. monocytogenes has been shown to require a two-component signal transduction system, which is essential for sensing different environmental stresses (15). Both the acid shock response and the ATR have been suggested to promote L. monocytogenes survival in acidic foods (9) and in gastric fluids (16), thereby contributing to the ability of this bacterium to cause infection (49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A neutropenic-mouse model was used to demonstrate that oral administration of sodium bicarbonate shortly before intragastric inoculation significantly increased the severity of the resulting systemic infection by L. monocytogenes strain EGD (64). When the murine gastric pH was lowered through the use of acidified water, it was observed that acid-adapted cells enjoyed increased resistance relative to their unadapted counterparts (198). These results suggest that control of gastric pH through dietary practices or use of inhibitors of gastric acid secretion may be potential aggravating risk factors for food-borne listeriosis.…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
“…In these circumstances, the number of aerobes, anaerobes, and coliforms increases so that there is overgrowth of bacteria in the stomach. It has also been observed that neutralization of acid by food or bicarbonate decreases the infectious dose; for example, an increase in the pH of the stomach results in gastric transit of greater numbers of Listeria (44,63,64,198,205,258) while gastrectomy and chronic gastritis are risk factors for the development of intestinal tuberculosis (62). Interestingly, preadaptation under conditions similar to those encountered by Mycobacterium avium in its natural habitat allows the organisms to resist the acidic conditions of the stomach (20).…”
Section: Introductionmentioning
confidence: 99%